Etos Kerja Pedagang Cabai Di Pasar 46 Jalan Baru Sejinjang Kecamatan Jambi Timur Kota Jambi Di Tinjau Dari Etika Bisnis Islam - Sulis Wiranti Putri; H. Sissah; Ahmad Syahrizal (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to find out about the work ethic of chili traders at market 46 along Jalan Baru, East Jambi District, Jambi City. and can reveal the causes of violations of business ethics in the work ethic of market 46 chili traders. This research model uses a qualitative descriptive research model. From the results of this research, it was found that seven out of eight traders had implemented and had a good work ethic and were in accordance with the provisions of Islamic business ethics. However, in this case, one trader was found who did not comply with Islamic business ethics, namely in terms of serving and responding to complaints.